THE EFFECT OF ENERGY SUBSIDY AND THE NUMBER OF MOTOR VEHICLES ON ECONOMIC GROWTH IN INDONESIA - nisha selvia (JURNAL ECONOMICA : Research of Economic And Economic Education, 2025)
This research aims to analyze the effect of energy subsidies and the number of motorized vehicles on economic growth in Indonesia. The research background stems from the increasing need for energy as a result of population growth, the number of motorized vehicles, and dependence on non-renewable fossil energy. The method used is a quantitative approach with multiple linear regression analysis techniques using secondary data processed with the help of the Eviews 10 and SPSS 21 applications. The research results show that both energy subsidies and the number of motorized vehicles have a positive influence on economic growth, but are not statistically significant. The R-square value of 0.203 indicates that 20.3% of the variation in economic growth can be explained by these two independent variables, while the rest is influenced by other factors. These findings indicate that to encourage higher economic growth, it is necessary to diversify the factors driving growth beyond energy and motor vehicle variables.